Mortality of twin and singleton livebirths under 30 weeks' gestation: a population-based study. Issue 2 (6th October 2008) - Ray, B; Platt, M P Ward
Abstract : Objective: To determine the mortality rates of liveborn twins compared with singletons of less than 30 weeks' gestation in relation to gestational age, mode of delivery and year of birth in a geographically defined population. Study design: Comparison of early neonatal, late neonatal and infant death rates in 479 twin babies and 1538 singletons, liveborn between 23 and 29 completed weeks of gestation in the north of England over two epochs, 1998–2001 and 2002–5. Results: Twins and singletons had similar mortality rates except at the extreme of gestation (23–25 weeks) where twins had higher infant mortality (OR 2.04, 95% CI 1.37 to 3.02). This higher rate was attributable to early and late neonatal deaths (OR 1.86, 95% CI 1.28 to 2.72, and 2.11, 95% CI 1.13–3.94, respectively). When analysed in two epochs, the excess mortality was confined to babies born in 1998–2001. There was no effect of gender or chorionicity. Conclusions: The excess mortality among twins of less than 30 weeks' gestation was confined to neonatal deaths in babies of 25 weeks or less, and to the earlier epoch (1998–2001). In the modern era, there appears to be no excess mortality in neonates less than 30 weeks' gestation when compared with singletons.